Krisis Politik dan Pandangan Ekonomi Menjelang Pemilu 1997 - Rizkinta, Bryna; Baihaqi, Ahmad Fauzan; Ramadhan, Fauzan Syahru (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2025)
This writing aims to explain how to understand the political crisis in the 1997 election and the economic and business views ahead of the elections. This research uses a historical method involving topic selection, collection of historical sources or heuristics, verification of historical sources, interpretation, and historiography. This research shows that 1997 created a political crisis in various regions in Indonesia, such as Yogyakarta, Banjarmasin, and Madura, as well as economic concerns among various elements. This was manifested with violence and people resistance that resulted in loss of life due to people's dissatisfaction with the government. The economic situation during the political crisis leading to the 1997 election caused reactions from the government, academic researchers, and businesspeople who wanted the country's stability. On the government side, President Soeharto and academics such as Mari Pangestu were optimistic regarding the economy ahead of the election. Meanwhile, conglomerate Sofyan Wanandi was more careful about the election process. It can be concluded that the violence and riots during the 1997 election campaign gave rise to various views and discourses regarding the national economy from various elements.